Apical hypertrophic cardiomyopathy as a mask of acute coronary syndrome: a case series - D. Yu. Goncharova; G. R. Bikbaeva; A. A. Tukhbatova; I. S. Mullova; D. V. Duplyakov (Российский кардиологический журнал, 2022)
Apical hypertrophic cardiomyopathy (HCM) or Yamaguchi syndrome is a relatively rare subtype of HCM characterized by a left ventricular apex localization of the hypertrophy. In this case, chest pain can be erroneously interpreted as a manifestation of coronary artery disease. This article presents two cases of apical HCM in patients admitted with a diagnosis of acute coronary syndrome. Electrocardiogram revealed repolarization disorder and giant T wave inversion (up to 10 mm) in the precordial leads. Transthoracic echocardiography revealed local symmetric hypertrophy of the left ventricular apex, which made it possible to diagnose apical HCM. The coronary arteries in both patients were intact. The presented cases demonstrate a variant of apical HCM with chest pain as the leading clinical syndrome, which can often be the cause of overdiagnosis of acute coronary syndrome.